Dari Istana Babel ke Indonesia Masa Kini: Relevansi Spiritualitas Daniel bagi Penguatan Toleransi Dalam Moderasi Beragama - Anugerah Joyser; Yehuda Indra Gunawan (Sekolah Tinggi Teologi Ekumene Jakarta., 2025)
Indonesia's religious diversity is both a national treasure and a potential source of religious conflict if the government lacks a robust mechanism to regulate interfaith coexistence. In recent years, the government has attempted to foster tolerance and moderation among religious communities, but in reality, cases of interfaith intolerance remain frequent. These incidents of intolerance not only result in financial losses but also psychological trauma and a sense of insecurity in religious practice and worship. This fact indicates that tolerance in religious moderation and the implementation of the first principle of Pancasila,